Memerdekakan Hak Orang Terpinggirkan: Analisis Teologi Pembebasan terhadap Karya Yayasan Kristen untuk Kesehatan Umum - Tahamata, Marfan Ferdinanda; Nole, Otniel Aurelius; Julliard, Devrinho; Ay, Benaya Revelino Maxmilian Yohanes; Fay, Riki Sumardi (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2024)
The Christian Foundation for Public Health (YAKKUM) is a social foundation engaged in public health, focusing on all religious communities, including marginalized people who do not get justice. This research aimed to analyze how YAKKUM’s works to liberate the rights of marginalized people from the perspective of De La Torre’s liberation theology. This research used a qualitative descriptive analysis method with a literature review approach, observation, and interviews with credible participants. We found that YAKKUM is a social movement in the health sector that transforms the lives of people with services, empowerment, and guidance accompanied by compassion. Through work units, YAKKUM provides transformative services and empowers and guides marginalized people to live in peace and prosperity. YAKKUM’s efforts to liberate marginalized groups are tangible actions that manifest through a vertical relationship with God and are realized horizontally with fellow humans.